2017
DOI: 10.1007/s00404-017-4343-7
|View full text |Cite
|
Sign up to set email alerts
|

Double-balloon catheter for induction of labour in women with a previous cesarean section, could it be the best choice?

Abstract: IntroductionWe analysed the efficacy and safety of double-balloon catheter for cervical ripening in women with a previous cesarean section and which were the most important variables associated with an increased risk of repeated cesarean delivery.Materials and methodsWe designed an observational retrospective study of 418 women with unfavourable cervices (Bishop Score <5), a prior cesarean delivery, and induction of labour with a double-balloon catheter. Baseline maternal data and perinatal outcomes were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 29 publications
(26 reference statements)
4
27
0
13
Order By: Relevance
“…Table 4 compares the findings of these investigations with those of the present study. The present cohort was the second only to that of De Bonrostro et al 16 in terms of size (105 vs 418 women), with the remaining seven studies enrolling between eight and 50 women. Similar to the present study, three studies reported that cervical ripening with DBC was useful and safe, resulted in a two-fold increase in the initial Bishop score, with cesarean delivery rates of approximately 40%-50%, and no substantial increased risk of perinatal adverse events.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Table 4 compares the findings of these investigations with those of the present study. The present cohort was the second only to that of De Bonrostro et al 16 in terms of size (105 vs 418 women), with the remaining seven studies enrolling between eight and 50 women. Similar to the present study, three studies reported that cervical ripening with DBC was useful and safe, resulted in a two-fold increase in the initial Bishop score, with cesarean delivery rates of approximately 40%-50%, and no substantial increased risk of perinatal adverse events.…”
Section: Discussionmentioning
confidence: 89%
“…Table compares the findings of these investigations with those of the present study. The present cohort was the second only to that of De Bonrostro et al . in terms of size (105 vs 418 women), with the remaining seven studies enrolling between eight and 50 women.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It allows cervical ripening, causing less uterine overstimulation [1]. Cases of oligohydramnios, fetal growth restriction, pregnancy complicated with asthma, hypertension, and uterine scarring favor a balloon catheter for cervical ripening due to the high risk of using prostaglandins [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%